Financial Literacy Assessment of Domestic and Foreign Young Learners and Recommendations for its Enhancement - Svetlana S.; Vladimir V. (National Research Mordova State University, 2018)
Introduction: the article considers the factors that determine the financial education of young people. Modern young men and women have a low financial literacy, despite the efforts for improving financial competence. This situation may threaten their personal and public financial security. The article proposes a new methodology for the theoretical and practical training of the young generation in making well-balanced and informed financial decisions. Materials and Methods: the domestic and international scientific literature on financial education has highlighted several approaches to the problem. The analysis of methods with comparison of domestic and foreign pedagogic theory and practice was made in the paper. The tests and questionnaires were developed by the authors to assess the financial literacy of students and schoolchildren. Results: insufficient level of financial competence of young people is revealed. The structure of the new curriculum on obtaining financial knowledge by high school students and university students is presented. Recommendations on the use of tests to assess the level of financial competence of young people are proposed. The study results were verified in high schools and at the University. The new methodology demonstrated its effectiveness. Discussions and Conclusions: modern educational programmes should comply with and meet the challenges of a current dynamically evolving society. The modern changing world pays more attention to financial aspects of human activities. The practical importance of the study lies in the use of new intellectual approaches to teaching financial competence in high schools and universities. The proposed recommendations on the organisation of financial education for the young people in Russia contribute to the formation of financial literacy and skills of students and seniour schoolchildren. The results of the research can be useful to specialists in the field of education and the scholarly public.